2021
DOI: 10.3390/biomedicines9080955
|View full text |Cite
|
Sign up to set email alerts
|

Synthesis and Biological Evaluation of Hydroxylated Monocarbonyl Curcumin Derivatives as Potential Inducers of Neprilysin Activity

Abstract: Background: Alzheimer’s disease (AD) involves impairment of Aβ clearance. Neprilysin (NEP) is the most efficient Aβ peptidase. Enhancement of the activity or expression of NEP may provide a prominent therapeutic strategy against AD. Aims: Ten hydroxylated monocarbonyl curcumin derivatives were designed, synthesized and evaluated for their NEP upregulating potential using sensitive fluorescence-based Aβ digestion and inhibition assays. Results: Compound 4 was the most active one, resulting in a 50% increase in … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
6
0
1

Year Published

2021
2021
2024
2024

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 9 publications
(7 citation statements)
references
References 47 publications
0
6
0
1
Order By: Relevance
“…Гидроксилированные производные монокарбонилкуркумина, содержащие циклогексанон, повышают уровень NEP [180]. В совокупности эти данные позволяют предположить, что куркумин обладает многоцелевой активностью и требует дальнейшего изучения.…”
Section: потенциальные нейропротекторные препараты воздействующие одн...unclassified
See 1 more Smart Citation
“…Гидроксилированные производные монокарбонилкуркумина, содержащие циклогексанон, повышают уровень NEP [180]. В совокупности эти данные позволяют предположить, что куркумин обладает многоцелевой активностью и требует дальнейшего изучения.…”
Section: потенциальные нейропротекторные препараты воздействующие одн...unclassified
“…In vivo and in vitro experiments revealed another mechanism of curcumin-induced reduction of Aβ accumulation and deposition: suppression of BACE1 expression [ 178 , 179 ]. Hydroxylated derivatives of monocarbonyl curcumin containing cyclohexanone increase NEP levels [ 180 ]. Taken together, these data suggest that curcumin exhibits multi-targeted activity and warrants further study.…”
Section: Potential Neuroprotector Agents Acting On Both Aβ Deposition...mentioning
confidence: 99%
“…Dimitris Matisdis synthesised numerous hydroxyl-bearing DZG derivatives and described them as good stimulants of the NEP enzyme. [55] Each analogue was evaluated for its ability to induce NEP expression at a maximum dose of 5 μM using two synthesised peptides qf-Aβ(1-7)C and qf-Aβ(12-16)AAC assay. Compound 80 (Figure 14) demonstrated the highest activity percentage (150.08) in the qf-Aβ(1-7)C assay, whereas compounds 81 and 82 (Figure 14) displayed the highest potency in the qf-Aβ(12-16)AAC-EDANS assay, with activity percentages of 124.48 and 125.10, respectively.…”
Section: Anti-alzheimer Activitiesmentioning
confidence: 99%
“…Amyloid plaques (Aβ) have been one of the major causes of Alzheimer's disease, and some studies suggested that the Neprilysin (NEP) enzyme reduces the Aβ peptide level. Dimitris Matisdis synthesised numerous hydroxyl‐bearing DZG derivatives and described them as good stimulants of the NEP enzyme [55] . Each analogue was evaluated for its ability to induce NEP expression at a maximum dose of 5 μM using two synthesised peptides qf‐Aβ(1‐7)C and qf‐Aβ(12‐16)AAC assay.…”
Section: Anti‐alzheimer Activitiesmentioning
confidence: 99%
“…(1E,4E)-1,5-bis (4-hydroxy-3-methoxyphenyl) penta-1,4-dien-3-one 6f [52] Orange solid, Yield: 2.15 g (66%), 1…”
Section: Synthesis Of Compounds 6f-hmentioning
confidence: 99%